Isotopic trends of nuclear surface properties of spherical nuclei; Physical Review C; Vol. 94, iss. 5 - Adamyan G. G. Gurgen Grigorjevich; Antonenko N. V. Nikolay Viktorovich; Lenske H.; Tolokonnikov S. V. Sergey Vladimirovich; Sapershteyn E. E. Eduard Evseevich (2016, 2016)
Title screen